Acrodermatitis enteropathica, a discussion and report of a case successfully treated - Wray, Joe D.; Günalp, Altan; Bertan, Münevver (The Turkish Journal of Pediatrics, 1959)
A brief discussion of acrodermatitis enteropathica has been presented with a case report of an infant with typical findings of this disease who was recently admitted to the Hacettepe Children’s Hospital. This is the first recorded instance of the occurrence of this disease in Turkey. The child was subjected to a therapeutic trial with nystatin in the hope of obtaining additional information concerning the role of C. albicans in this interesting disease. Nystatin was found to be thoroughly effective in eliminating C. albicans, but this had no effect on the primary skin lesions. Subsequent therapy with Diodoquin confirmed previous reports of its effectiveness in the management of acrodermatitis enteropathica.